2010
DOI: 10.1097/prs.0b013e3181d62a94
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Injury in Plastic Surgeons

Abstract: Self-reported injury is more prevalent in surgery than in previously described, labor-intensive populations. Sampled surgeons appear younger than the general surgery workforce, and as a result, this study may underestimate the prevalence of occupational injury, particularly carpal tunnel syndrome. This study underscores the need for a formal, multicenter assessment of occupational injury in surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 14 publications
4
88
1
Order By: Relevance
“…Additional analysis was conducted on the neck, back, and shoulder postures, areas with high prevalence of musculoskeletal pain and disorders among surgeons who used optical magnification (Capone et al 2010; Sivak-Callcott et al 2011; Statham et al 2010). Postural shifts in the included neck angle (Table 1) were 3.22 times more frequent (p<0.05) on the Video3D than Micro3D (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional analysis was conducted on the neck, back, and shoulder postures, areas with high prevalence of musculoskeletal pain and disorders among surgeons who used optical magnification (Capone et al 2010; Sivak-Callcott et al 2011; Statham et al 2010). Postural shifts in the included neck angle (Table 1) were 3.22 times more frequent (p<0.05) on the Video3D than Micro3D (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Work-related musculoskeletal pain, fatigue, and discomfort can affect both the comfort of surgeons and their ability to complete surgical tasks; yet, the reported prevalence of musculoskeletal symptoms in the neck, back, and shoulders is as high as 87% among surveyed laparoscopic, ophthalmic, and general surgeons (Davis et al 2014; Capone et al 2010; Park et al 2010; Sivak-Callcott et al 2011; Szeto et al 2009; Wauben et al 2006). Furthermore, a survey of 130 ophthalmic surgeons who frequently used magnification, e.g., loupes and microscopes, showed that 9.2% of surgeons stopped operating due to neck pain (Sivak-Callcott et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 As a result, chronic poor posture and musculoskeletal strain can lead to increased rates of disability and reduced surgical longevity. 24 …”
mentioning
confidence: 99%
“…In addition, the weight of the system limits the duration of filming as it may induce surgeon neck strain. [3][4][5][6] This is particularly true during cases where the surgeon will be wearing magnifying loupes, head-mounted lighting sources, or both. The recording system would also benefit from a different lens with greater magnification.…”
Section: Discussionmentioning
confidence: 98%